Analisis Yuridis Terhadap Pelaksanaan Pinjam Pakai Barang Bukti Perkara Tindak Pidana - Yeni Suswita; Hery Fadlullah; Nurjannah Nurjannah; Pasten Hard; Marsudi Utoyo (Lex Stricta : Jurnal Ilmu Hukum, 2023)
The court conducts an examination process known as proof. For the purposes of proof, the presence of objects involved in a crime is also very necessary. These objects are often known as "evidence". The problem in this study is how investigators are responsible for evidence. What is the Process of Borrowing and Using Evidence in Criminal Cases. The research methodology is descriptive, namely normative juridical research. The results of the investigation show that the investigator's responsibility for evidence starts from the moment the item is confiscated by the investigator, so since then if the evidence is damaged or lost, then this responsibility is the responsibility of the investigator at the investigation level. The process of borrowing and using evidence in criminal cases can be carried out by the owner of the evidence based on KAPOLRI Regulation Number 10 of 2010 concerning Procedures for Managing Evidence within the POLRI, in Chapter VI Procedures for Borrowing and Using Evidence by Owners. In conclusion, the investigator's responsibility for evidence starts from the moment the item is confiscated by the investigator, so since then if the evidence is damaged or lost and the Borrowing and Use of Evidence Process in a Criminal Case can be carried out by the owner of the evidence based on KAPOLRI Regulation Number 10 of 2010 concerning Management Procedures Evidence in the Police Environment. So that every application for borrowing evidence, the investigator can lend the evidence to the victimized party without asking for exorbitant fees. To victims or owners who want to borrow evidence to carry out the correct procedures in accordance with KAPOLRI Regulation Number 10 of 2010 to investigator superiors.